South Asian summer monsoon breaks: Process‐based diagnostics in HIRHAM5. Issue 9 (12th May 2017) - Hanf, Franziska S.; Annamalai, H.; Rinke, Annette; Dethloff, Klaus
Abstract: This study assesses the ability of a high‐resolution downscaling simulation with the regional climate model (RCM) HIRHAM5 in capturing the monsoon basic state and boreal summer intraseasonal variability (BSISV) over South Asia with focus on moist and radiative processes during 1979–2012. A process‐based vertically integrated moist static energy (MSE) budget is performed to understand the model's fidelity in representing leading processes that govern the monsoon breaks over continental India. In the climatology (June–September) HIRHAM5 simulates a dry bias over central India in association with descent throughout the free troposphere. Sources of dry bias are interpreted as (i) near‐equatorial Rossby wave response forced by excess rainfall over the southern Bay of Bengal promotes anomalous descent to its northwest and (ii) excessive rainfall over near‐equatorial Arabian Sea and Bay of Bengal anchor a "local Hadley‐type" circulation with descent anomalies over continental India. Compared with observations HIRHAM5 captures the leading processes that account for breaks, although with generally reduced amplitudes over central India. In the model too, anomalous dry advection and net radiative cooling are responsible for the initiation and maintenance of breaks, respectively. However, weaker contributions of all adiabatic MSE budget terms, and an inconsistent relationship between negative rainfall anomalies and radiative cooling reveals shortcomings in HIRHAM5's moisture‐radiation interaction. Our study directly implies that process‐based budget diagnostics are necessary, apart from just checking the northward propagation feature to examine RCM's fidelity to simulate BSISV. Key Points: Excess rainfall over tropical ocean regions contributes to climatological dry bias over central India in HIRHAM5 MSE budget shows that anomalous dry advection (radiative cooling) is the leading process in initiating (maintaining) breaks Inconsistent relationship between anomalous rainfall and radiative cooling during breaks suggests weak moisture‐radiation interaction